Study on the welfare effect of agricultural export policies in Kyongnam province on the real farm income level - Jung, Jae Min (KDI School, 2000)
Kyongnarn province has actively sought various agricultural export policies targeted at Japanese market for the growth of farm income and its regional economy. However, the effectiveness of such export subsidy provision on the actual welfare of farm households needs to be studied carefully. Brander and Spencer(1985) say that the government subsidy to a certain economic sector will enhance the welfare of both that subsidy recipient sector and the overall nation. Eaton and Grossman(1986) say that it will decrease the welfare of both that particular sector and the overall nation. Therefore, I am concerned about whether Kyongnam provinces' export policy is actually beneficial to its farm households' and Kyongnam provincial residents' welfare. Therefore, the purpose of this paper is to answer whether Kyongnarn province's export policy is actually beneficial to its farm households' and Kyongnarn provincial residents' welfare. I analyze and evaluate it through as the followed cases; (1) the real farm income of households that produces the export items (2) the real farm income of households that produces non-export items.(3) the welfare effects of Kyongnarn provincial resident.
Thesis(Master) --KDI School:Master of Economics and Public Policy,2000